Pembinaan Ideologi Pancasila dan Wawasan Kebangsaan Bagi Kalangan Muda di Kabupaten Wonogiri - Aziz Widhi Nugroho; Retno Eko Mardani; Rengga Kusuma Putra; Satriya Nugraha; Linda Ikawati; Bagus Hermanto; Sandra Leoni Prakasa Yakub; Dian Karisma; Sitta Saraya; Dian Ratu Ayu Uswatun Khasanah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
A clear national insight can guarantee the achievement of national interests, both internally and externally. This means that national insight provides a clear picture and direction for the nation's survival, as well as the future development of the nation and state. The organization of national and state life must proceed on the basis of mutual agreement, namely Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia (NKRI), and Bhinneka Tunggal Ika (Unity in Diversity). Indonesia's existence as a state based on the rule of law (rechtstaat) based on Pancasila and the 1945 Constitution requires the development of Pancasila ideology and national insight as instruments that serve as catalysts or drivers in strengthening national insight and spirit, love of the homeland, democracy, legal awareness, respect for diversity, and participation in building a Pancasila-based nation in Wonogiri, especially among intellectuals. In accordance with its function, the Pancasila Ideology and National Insight Development organizes national, democratic, legal, multicultural and citizenship education to support the realization of citizens who are aware of their rights and obligations, as well as intelligent, skilled and have character so that they can be relied upon to build the nation and the Unitary State of the Republic of Indonesia.